2009
DOI: 10.3892/ijmm_00000259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local vibrations on skeletal muscle trophism in elderly people: mechanical, cellular, and molecular events

Abstract: Abstract. Several studies have examined the effects of vibrations on muscle mass and performance in young healthy people. We studied the effects of vibrations on muscles of elderly male and female volunteers (65-85 years of age) diagnosed with sarcopenia. We applied mechanical vibrations locally (local vibrational training) to the thigh muscles at 300 Hz for a period of 12 weeks, starting with a session of 15 min stimulation once a week and increasing to three sessions of 15 min per week. Treated muscles displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 50 publications
3
76
0
Order By: Relevance
“…Proteins prepared from TPNB samples were subjected to gel electrophoresis and Western blotting. Notably, residual samples after single-fiber dissection could also be used in protein analysis, as described in Materials and methods) (7,17). Our collection procedure facilitated the initial homogenization required for protein solubilization, and we thus obtained protein quantities that were more than sufficient for electrophoresis and subsequent immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Proteins prepared from TPNB samples were subjected to gel electrophoresis and Western blotting. Notably, residual samples after single-fiber dissection could also be used in protein analysis, as described in Materials and methods) (7,17). Our collection procedure facilitated the initial homogenization required for protein solubilization, and we thus obtained protein quantities that were more than sufficient for electrophoresis and subsequent immunoblotting.…”
Section: Resultsmentioning
confidence: 99%
“…High-quality RNA was processed. RNA aliquots of 2 μg were used for amplification and labeling prior to application to a high-density oligonucleotide microarray (10,17,23). Aliquots of 2 μg RNA were used for retrotranscription and loading to multigene arrays prior to PCR analysis (Applied Biosystems/Life Technologies; array no.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with high-intensity focused acoustic waves is based on the action of vibrations, which allow, in selected muscle groups, to optimize muscular tone, increase muscle strength and endurance to repeated exercise, and improve coordination, producing a positive muscular activity without causing damage. Local high-intensity vibration may also improve muscular strength influencing the levels ofparticular hormones, and ameliorate neuromuscular performance; Saggini et al (26) demonstrated the short-and long-term effects of high-intensity focused vibration, showing that focused vibration can influence the levels of specific substances, such as growth hormone, creatine phosphokinase, and cortisol, resulting in significant improvements in neuromuscular performance, comparable to that of endurance; local high-intensity vibration may also counteract the loss of muscle strength in both young patients and elderly subjects suffering from sarcopenia (27). The long-term beneficial effects ofhigh-intensity focused acoustic waves have been shown to be particularly striking when local high-intensity vibration has been combined with eccentric training (28).…”
Section: Discussionmentioning
confidence: 99%